Sharia Banking Rights and Obligations in Implementing Musyarakah Agreements Based on Indonesian Law - Faisal Faisal (International Journal Reglement & Society (IJRS), 2020)
Islam brings a view or way of life that regulates all aspects of human life, so there is no single aspect of human life apart from Islamic teachings, both from the legal aspect to the economic aspect. In this modern era, economic activity will not be perfect without the existence of a banking institution, this banking institution is also a must. This agreement gives birth to the engagement so that it can be called a contract. This research uses a type and research approach using normative legal research (normative juridical). Normative legal research is also called doctrinal legal research, where law is conceptualized as what is written in statutory regulations (law in books). Legal research aims to identify and describe the state of something regarding the existence of legal norms and the operation of legal norms in society. Based on the objectives of legal research, the tendency of the nature of the research used is descriptive. Based on Article 4 paragraph (3) letter a of Bank Indonesia Regulation Number 19/4 / PBI / 2017 concerning Sharia Short-Term Liquidity Financing for Sharia Commercial Banks, Financing Assets must meet the requirements, one of which is financing with a mudharabah contract, a musyarakah contract, and / or a contract. ijarah non service. That the rights and obligations (Bank and mudharib), among others, provide capital and work based on the agreement at the time the contract is made, gain profits based on the agreed ratio, bear losses in proportion to the capital, the first party (syarik) is obliged to promise to sell all hishshah gradually and the second party (syarik) is obliged to buy it; and after completion of sales settlement, all LKS hishshah switch to other syarik (customer).